The manufacture ecosystem towards green economic growth: A per capita income perspective in Vietnam - Le, Thi Thuy Hang; Nguyen, Tuan Duy; Tran, Ngoc Thien Anh; Huynh, Gia Hue; Pham, Vu Song Hao; Vu, Ngoc Anh Thu (Journal of Finance - Marketing Research, 2025)
This study examines and evaluates the interaction between the production ecosystem, green growth and the per capita income during Vietnam’s economic transition toward a green economy. To ensure the accuracy of the result, annual time-series data include GDP per capita (USD), agricultural production value (million VND), and carbon dioxide emissions (metric tons) from 2000 to 2022 are taken from reliable secondary source like World Bank. The study effectively applied quantile-quantile regression model, giving the most comprehensive results that when the per capita GDP increases by 1 unit, CO₂ emissions increase by approximately 0.3864 metric tons and when agricultural output increases by 1 unit, CO₂ emissions increase by about 0.37 metric tons. Although Vietnam has made significant progress toward economic growth, this development has been accompanied by increasing CO₂ emissions and environmental pollution. Also, there are limited empirical evidence exists for Vietnam that integrates per capita income, agricultural production, and carbon emissions within a green growth framework. In addition, it is necessary to balance maintaining the annual growth rate of per capita income and finding a model suitable for Vietnam’s production ecosystem to achieve the set goals in the global integration period.